THEORETICAL FOUNDATIONS FOR REGULATING THE STATUS OF SECURITY AND DEFENSE FORCES PERSONNEL (SERVICE MEMBER, EMPLOYEE, STAFF MEMBER) - Yemanov, Vladyslav; Batiuk, Oleh; Bielai, Serhii (Honor and Law, 2024)
A study on the status of security and defense forces personnel was conducted. The etymological meanings of the terms "service member," "employee," and "staff member" were analyzed, as well as the perspectives of leading scholars on these terms. Based on this analysis, the author formulated proposals for regulating the status of security and defense forces personnel. Through the analysis of Ukraine’s regulatory framework, the norms defining the legal status of service members, employees, and staff members were summarized. Further research directions were identified, aimed at examining the relationship between the statuses of personnel in the security and defense sectors of Ukraine, including "service member," "civil servant," and "employee."